Tumor Necrosis Factor-Alpha and Age-Related Pathologies - S. V. Topolyanskaya (SINAPS LLC, 2020)
Modern concepts about the «inflammaging» and the role of subclinical inflammation in various age-associated pathology are described in the review. Particular attention is paid to the tumor necrosis factor-α, a key cytokine that plays an important role in the pathogenesis of chronic inflammatory diseases as well as in aging. The increased levels of tumor necrosis factor-α leads to the onset and progression of various diseases, to severity of frailty, to disability and mortality of elderly persons. Tumor necrosis factor-α affects different risk factors for cardiovascular diseases, contributes to the onset and progression of atherosclerosis and related pathology. This cytokine can also aggravate various metabolic disorders, mainly - insulin resistance and diabetes mellitus. Tumor necrosis factor-α is a key cytokine that stimulates bone resorption (up to osteoporosis) and sarcopenia (up to cachexia). Currently available data confirm the important role of tumor necrosis factor-α in various age-associated disorders.